The Importance of Self-Realization and Its Relation to the Progress of Man and Society in Islam: Some Reflections on Muhammad Iqbal's Concept of Selfhood - Abdul Rahim, Adibah (2008)

(untitled)
One of the main reasons for Muslims’ decadence was the philosophical system which inculcates self-negation and self-abandonment. This system advocates an attitude of lack of interest in action, renunciation of the world, and an asceticism which are against the original spirit of Islam. Iqbal was opposed to this system, and he introduced a unique concept of khudi or selfhood. The concept of self is the most important views to be discussed because it is the central idea of his philosophy on which the rest of his thought-structure is based. For Iqbal, understanding the nature of the self is essential for an understanding of the nature of society and the principle of its growth. Self, according to Iqbal, is an active and creative force in which a person should strive towards the achievement of a rich personality as well as participate in the affairs of the universe to suit his highest position as the vicegerent of God on earth. This is in line with the Qur’anic perception of man as an ascending spirit who is capable of changing the entire course of history. Thus, the moral and religious ideal of man, according to Iqbal, is not self-negation, but it must be self-assertion or self-realization. This paper attempts to discuss the nature of the self as expounded by Iqbal and how the self grows into a strong and powerful personality. Iqbal does not only preach self-realization by individuals, but his idea also prescribes suppression of individualism, which precludes any collective and concerted effort. Iqbal has recognized a necessary relationship between the individual and society. He sees society as a must for the proper growth and development of human and it is only in society that man can achieve self-realization. It is at this juncture that this paper also tries to discuss the nature of mutual relationship between the individual and society wherein man lives, moves, and exists.